Can Tour de Singkarak Be Held in Sumedang An Implementation Study - Muhamad Rizki Aditya; Tedi Supriyadi; Rizal Ahmad Fauzi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study analyzes the readiness of Sumedang Regency in organizing international sport tourism events such as Tour de Singkarak. Sumedang has supporting geographical and cultural potential, but it needs in-depth studies related to infrastructure, government support, and community and private sector participation. The methods used are literature studies and in-depth interviews with the Head of Disparbudpora and the local community. The results of the study show that Sumedang has potential routes for cycling in the Jatigede, Kampung Toga, and Gunung Tampomas areas. However, supporting infrastructure such as roads, public facilities, and accommodation still need to be improved. This event has the potential to improve the local economy through the culinary and accommodation sectors, but sponsorship support still needs to be strengthened. The community welcomed this event, with the hope of improving facilities and training. Environmental sustainability is also a major concern, especially in waste management. In conclusion, Sumedang has great potential as a host for sports tourism events, but requires infrastructure improvements, promotional strategies, and further collaboration between the government, community, and private sector in order to optimize the potential for sports tourism and improve the regional economy.